THE MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN MELALUI MEDIA TEBAK WARNA GAMBAR DI TK IT ABATATSA PASURUAN : MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 5-6 TAHUN MELALUI MEDIA TEBAK WARNA GAMBAR DI TK IT ABATATSA PASURUAN - Nadia Kaffiya Salsabila Samsyah; Agustiarini Eka Dheasari (incrementapedia, 2022)
Abstract Every child has their own way of solving simple problems in using objects in their daily lives. Children are able to use an object based on its function, and recognize various colors. Children's cognitive development can be developed from an early age in various ways. One of them is through the media. Learning media can be used to stimulate aspects of children's cognitive development. Media guess the color of the image is a medium that is used to develop cognitive aspects. This research is a classroom action research (CAR). The research subjects were group B children aged 5-6 years at TK IT Abatatsa Pasuruan. The results of research using guessing color media show that this media can improve cognitive abilities in early childhood. When children play media, children can solve problems by differentiating the colors of the images. So that learning while playing through the media is more fun and further enhances aspects of child development. After using the media, children's cognitive development increased with very good development results obtained by 85%, namely 15 children. Developing according to expectations of 15%, namely 3 children.